The importance of animal models in tumor immunity and immunotherapy - Budhu, Sadna (Curr Opin Genet Dev, 2013)
The clinical success and US FDA approval of two immunotherapies (sipuleucel-T and ipilimumab) have brought tumor immunology to the forefront of cancer research. It has been long recognized that the immune system can infiltrate and survey the tumor microenvironment. The field of tumor immunology has been actively examining this phenomenon since the 1890s when William Coley first treated patients with live pathogenic bacteria and observed occasional regressions leading to long term survival. Recent progress in understanding mechanisms of immune activation and tolerance has led to the development of novel therapies that aim to either overcome inhibitory pathways (i.e. checkpoint blockade such as anti-CTLA-4 and anti-PD-1) or stimulate immune cell activation (i.e. co-stimulation such as anti-GITR and anti-OX40). A major part of the success of immunotherapy has been the development of appropriate mouse models. This review will outline the history and the major findings leading to the accomplishments of modern day immunology with specific attention to the usefulness of animal models.